2000
DOI: 10.1557/jmr.2000.0093
|View full text |Cite
|
Sign up to set email alerts
|

A solvothermal route to wurtzite ZnSe nanoparticles

Abstract: Zinc powder reacts with equivalent elemental selenium in solvent ethylenediamine at 120 °C for 6 h to form a complex, which is converted to ZnSe nanoparticles by pyrolysis or protonization. X-ray diffraction results suggest that the as-formed products have wurtzite structure. Transmission electron microscopy observation show that particles with spherical and laminar morphology were produced by pyrolysis and protonization, respectively. The formation of ZnSe nanoparticles is also investigated by infrared and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
7
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 19 publications
3
7
0
Order By: Relevance
“…Qian and coworkers [66] have reported wurtzite ZnSe nanoparticles with sizes in the 18 nm range starting from the elements in ethylenediamine (T ¼ 120 C, t ¼ 6 h.) This reaction yields a complex with the formula ZnSe(en) where en is ethylenediamine. Seshadri has used toluene as the solvent in a neat preparation of CdSe from cadmium stearate and Se powder [67,68], tetralin (tetrahydronaphthalene) was added as a reducing agent.…”
Section: Hydrothermal and Solvothermal Methodsmentioning
confidence: 99%
“…Qian and coworkers [66] have reported wurtzite ZnSe nanoparticles with sizes in the 18 nm range starting from the elements in ethylenediamine (T ¼ 120 C, t ¼ 6 h.) This reaction yields a complex with the formula ZnSe(en) where en is ethylenediamine. Seshadri has used toluene as the solvent in a neat preparation of CdSe from cadmium stearate and Se powder [67,68], tetralin (tetrahydronaphthalene) was added as a reducing agent.…”
Section: Hydrothermal and Solvothermal Methodsmentioning
confidence: 99%
“…A mono-dentate ligand, n-butylamine, was found to be a shape controller for nanorods of CdS and MSe (M ¼ Zn, Cd or Pb) [101]. Similarly, the precursor of ZnE(en) 0:5 (E ¼ S, Se) could also form in en which then is converted to ZnSe nanoparticles via pyrolysis in solvothermal conditions [102]. The coordinating ability of the solvent was found to play an important role in the nucleation and growth of nanocrystallites [103].…”
Section: Synthesis Of One-dimensional Metal Chalcogenide Nanocrystallmentioning
confidence: 99%
“…Traditionally, CdSe is prepared through solid-state reaction between elemental cadmium and selenium at high temperature [3]. Recently, many wet chemical methods have been applied to synthesize CdSe, and the most noticeable two methods are colloidal method (Alivisatos's and Peng's group) [2,[4][5][6] and hydrothermal/solvothermal technique (Qian's group) [7][8][9][10][11][12][13][14]. Peng et al [6] synthesized high quality nanocrystals using CdO as precursor.…”
mentioning
confidence: 99%
“…Many researchers has reported CdSeC 2 -N 2 H 8 complex formed before decomposing into CdSe in ethylenediamine, which exhibited a strong peak near 2h ¼ 10°in the XRD pattern [12,16]. It has been reported that the complex is stable in neutral aqueous solutions but decomposes in dilute acid solutions [11]. So the precursors can be decomposed into CdSe nanocrystals by two methods: solvothermal treatment and protonization in dilute acid solution.…”
mentioning
confidence: 99%
See 1 more Smart Citation